Conjoint analysis jako sposób wyznaczania wag cech rynkowych w wycenie rynkowej nieruchomości za pomocą podejścia porównawczego - Pawlukowicz, Roman; Bartłomowicz, Tomasz (Conjoint analysis as a way to set balances of market features in properties estimating procedure using comparative methods, 2005)
The major parameters of the real properties estimating procedure using comparative methods (pair comparison method and correction of average price method) are balances of market features. The results of the specified real property estimation, which was based on the similar real properties, using identical set of market features but different structure of their balances, may vary significantly. So it is important for the reliability of the real properties estimation based on mentioned comparative methods, that the balances of market features are correctly found. The paper presents the possibilities - integrated in Standard III 7. of the PFSRM professional real properties experts - of finding the balances of market features using conjoint analysis method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 128-139